Penerapan Model Talking Stick Dalam Upaya Meningkatkan Motivasi Belajar Siswa - Waudy, Safrida Nafitupulu, Karen (Lembaga Penelitian dan Pengabdian Masyarakat, 2023)
The aim of the research is to find out how the talking stick method can increase students' learning motivation in mathematics subjects in class II of SD Negeri 107105 Kuta Baru. The method used in this research is qualitative research and the type of research used is classroom action research carried out over 3 cycles, each cycle consisting of 2 meetings. and the subjects of this research were class II students at SD Negeri 107105 Kuta Baru. The research instruments used were observation sheets, questionnaires, test question sheets. The results of this research show that the application of the talking stick method can increase students' learning motivation in mathematics subjects in class II of SD Negeri 107105 with the following results. The results of this research show that the application of the talking stick method can increase students' learning motivation in mathematics subjects in class II of SD Negeri 107105 with the results can be seen from the average score of students' learning motivation in cycle I which was obtained at 70 with the highest score being 87 and the lowest score 57, and in cycle II there was a change in the average score of student learning motivation of 83 with the highest score being 98 and the lowest score being 62.